Adoption of evidence-based global policies at the national level: intermittent preventive treatment for malaria in pregnancy and first trimester treatment in Kenya, Malawi, Mali and The Gambia. Issue 10 (12th November 2020) - Webster, Jayne; Hoyt, Jenna; Diarra, Samba; Manda-Taylor, Lucinda; Okoth, George; Achan, Jane; Ghilardi, Ludovica; D'Alessandro, Umberto; Madanista, Mwayi; Kariuki, Simon; Kayentao, Kassoum; Hill, Jenny
Abstract: In 2012, the World Health Organization (WHO) updated its policy on intermittent preventive treatment in pregnancy with sulphadoxine–pyrimethamine (IPTp-SP). A global recommendation to revise the WHO policy on the treatment of malaria in the first trimester is under review. We conducted a retrospective study of the national policy adoption process for revised IPTp-SP dosing in four sub-Saharan African countries. Alongside this retrospective study, we conducted a prospective policy adoption study of treatment of first trimester malaria with artemisinin combination therapies (ACTs). A document review informed development and interpretation of stakeholder interviews. An analytical framework was used to analyse data exploring stakeholder perceptions of the policies from 47 in-depth interviews with a purposively selected range of national level stakeholders. National policy adoption processes were categorized into four stages: (1) identify policy need; (2) review the evidence; (3) consult stakeholders and (4) endorse and draft policy. Actors at each stage were identified with the roles of evidence generation; technical advice; consultative and statutory endorsement. Adoption of the revised IPTp-SP policy was perceived to be based on strong evidence, support from WHO, consensus from stakeholders; and followed these stages. Poor tolerability of quinine was highlighted as a strong reason for a potential change in treatment policy. However, the evidence on safety of ACTs in the first trimester was considered weak. For some, trust in WHO was such that the anticipated announcement on the change in policy would allay these fears. For others, local evidence would first need to be generated to support a change in treatment policy. A national policy change from quinine to ACTs for the treatment of first trimester malaria will be less straightforward than experienced with increasing the IPTp dosing regimen despite following the same policy processes. Strong leadership will be needed for consultation and consensus building at national level.